السياسة الاستثمارية في ليبيا وتحديات الاقتصاد الأخضر - الحويج, حسين فرج (جامعة الوادي - University of Eloued, 2023)
The aim of this study is to analyze whither the investment policy in the Libyan economy is compatible with the requirements of practicing green economy principles. Using annual data covering the period 1990-2019 the study adopted augmented autoregressive distributed lags ARDL model. According to the main findings, a long run equilibrium relationship between the study variables was captured. Theses variables are investment as an independent variable, and environmental degradation proxied by CO2 emissions as a dependent variable. In addition, the study indicated a positive long run impact of investment on CO2 variable. Toda-Yamamoto non Granger causality test results supported a unidirectional causal relationship from investment to CO2 emissions.
Investment policyin Libya and green economy challenges
مقال
Keywords: السياسة الاستثمارية ; الاقتصاد الأخضر ; الانحدار الذاتي ; الاقتصاد الليبي; investment policy, green economy, autoregressive, Libyan economy.